Foam dressings for treating pressure injuries in patients of any age in any care setting: An abridged Cochrane systematic review. (November 2018) - Walker, Rachel M.; Gillespie, Brigid M.; Thalib, Lukman; Higgins, Niall S.; Whitty, Jennifer A.
Abstract: Background: Pressure injuries are localised areas of injury to the skin and/or underlying tissues. Objectives: To assess foam dressings compared to other dressings in healing pressure injuries. Design: Systematic review and meta-analysis Data sources: The review team searched: the Cochrane Wounds Specialised Register; the Cochrane Central Register of Controlled Trials; Ovid MEDLINE; Ovid Embase; EBSCO CINAHL Plus and the NHS Economic Evaluation Database. Authors also searched clinical trials registries and scanned reference lists for reviews, meta-analyses and health technology reports. No restrictions were applied to language, publication date or study setting. Study eligibility criteria: Published or unpublished randomised controlled trials and cluster- randomised controlled trials that examined the clinical or cost effectiveness of foam dressings for healing pressure injuries. Participants: Patients of any age with a pressure injury of Stage II or above in any care setting. Interventions: Use of any foam wound dressing for treating Stage II pressure injuries or above. Study appraisal and synthesis methods: Full-text were assessed for eligibility using a priori criteria by two authors. Risk of bias was assessed using the Grading of Recommendations, Assessment, Development and Evaluation criteria, and Consolidated Health Economic Evaluation Reporting Standards. Risk ratio and mean difference with 95% confidence intervals were used to measure the effect. The review team used Review Manager 5 to enter narrative and qualitative data of included studies. Results: Authors found nine studies published between 1994 and 2016 involving 483 participants with pressure injuries at Stage II or above. Included studies compared foam dressings with other types of dressings. However, it was unclear if the foam dressing affected healing (RR 1.00, 95% CI 0.78–1.28), time to complete healing (MD 5.67 days 95% CI-4.03–15.37), adverse events (RR 0.33, 95% CI 0.01–7.65), or reduction in pressure injury size (MD 0.30 cm 2 per day, 95% CI −0.15 to 0.75), as the certainty of the evidence was very low. Limitations: Using the Grading of Recommendations, Assessment, Development and Evaluation criteria, the certainty and completeness of evidence was low to very low, making it difficult to draw comparisons between foam and other dressings. Conclusions and implications: It is uncertain whether foam dressings are more clinically effective, more acceptable to users, or more cost effective compared to alternative dressings in treating pressure injuries.